Nanofibrillation is an Effective Method to Produce Chitin Derivatives for Induction of Plant Responses in Soybean - Hironori Kaminaka; Chihiro Miura; Yukiko Isowa; Takaya Tominaga; Mamu Gonnami; Mayumi Egusa; Shinsuke Ifuku (Plants, 2020)
Chitin, an N-acetylglucosamine polymer, is well-known to have unique biological functions, such as growth promotion and disease resistance induction in plants. Chitin has been expectedly used for improving crop yield using its functions; however, chitin derivatives, such as chitin oligosaccharide (CO) and chitosan, are widely used instead since chitin is difficult to handle because of its insolubility. Chitin nanofiber (CNF), produced from chitin through nanofibrillation, retains its polymeric structure and can be dispersed uniformly even in water. Here, the effects of CO and CNF on plant responses were directly compared in soybeans (Glycine max) to define the most effective method to produce chitin derivatives for plant response induction. The growth promotion of aerial parts was observed only in CNF-treated plants. The transcriptome analysis showed that the number of differentially expressed genes (DEGs) in CNF-treated soybeans was higher than in CO-treated soybeans. Notably, the expression patterns of DEGs were mostly similar but were strongly induced by CNF treatment as compared with the CO group. These results reveal that CNF can induce stronger plant response to chitin than CO in soybeans, suggesting nanofibrillation, rather than oligomerization, as a more effective method to produce chitin derivatives for plant response induction.